Rynek żywca wieprzowego w Polsce po wstąpieniu do Unii Europejskiej - Juchniewicz, Małgorzata (Pigs' Market in Poland after the Access to the European Union, 2005)
The prices of Polish pork after its access to the European Union have grown gradually to a level of the cheapest manufacturers in EU. However, this resulted mainly from hesitations in economic situation and not from the access. In future one should not expect a decrease of the price variation, because in spite of many years' intervention activities in the member countries prices are often below the basis ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 371-376